An exploration of Lavender Hill's youth pathways to employment - Kanengoni, Miriam (Department of Social Development, 2017)
The world is confronted by a worsening youth unemployment crisis. Young people are more likely to be unemployed than adults. Youth employment is important for economic and social stability and growth. Though youth face numerous challenges, many are determined to succeed and are using varied approaches to ensure their 'survival'. The purpose of this qualitative research study was therefore to explore these varied approaches employed by young people to gain access into the world of work. Seventeen face to face interviews were conducted with young people who matriculated from Lavender Hill High School in Lavender Hill community. The study focused specifically on how the research participants negotiated their pathways to employment in the labour market. The study indicated attitudes and sources of motivation for youth towards finding employment which were driven by several factors. The main factor was the need to improve standards of living and escape the socials ills that are plaguing Lavender Hill community. Such ills include gang violence, crime, substance and alcohol abuse, lack of positive role models, financial constraints, school dropouts as well as teenage pregnancies. These ills also came up as the challenges faced by the young participants on their pathways to employment. The participants managed to utilise a range of support systems that were available to them, from government interventions, social networks from school, churches, NGOs and private companies, to recruitment agencies for them to be able to access employment. The importance of personal and technical skills was highlighted as the youth needed to have those skills to be able to get jobs. Recommendations included the need for, NGOs to advance their services for youth in career information and support them with instant education and training decisions; private companies partnering with local schools and post-secondary institutions to create platforms where the companies can speak to students about career opportunities and expected skills as well as mentoring them and offering placements that give young people the much needed skills and experience while they complete their high school, college, university or apprenticeship programs. Additionally, it was recommended that community members play their role in their societies through caring, serving, connecting, supporting and helping; government ministries to strengthen safety nets for youth in poor townships for them to counter the hindrances they face towards accessing jobs.